ANALISIS FAKTOR SOSIAL EKONOMI YANG MEMPENGARUHI PENDAPATAN BERSIH NELAYAN RAWAI DI KECAMATAN TELUK AMBON - Willem Talakua (LPPM Universitas Pekalongan, 2013)
One of the subdistricts in the city of Ambon, most people work as fishermen are Ambon Bay subdistrict. In these subdistrict there is a unit of long line effort that afforded by the local fishermen to the characteristics of small-scale businesses. The resulting production is sold and consumed by households fishing (subsistence farmer). This research aims to analyze the net income of fishermen and socioeconomic factors that affect net income of long line fishing. The data was collected through surveys and interviews, as well as from secondary data. Analysis of the data used is the analysis of income and multiple linear regressions. The results showed that the net income earned during the one year fishermen are Rp 45.556.046, and net income each month is Rp 3.796.337. While socioeconomic factors that affect long line fishermen net income are: investment costs (X1), operating costs (X2), fishing trip (X3), production (X4), and business experience (X5). Key words: Socioeconomic factors, net income, long line fishermen.